A systematic review of telemedicine interventions to support blood glucose self-monitoring in diabetes. - Farmer, A; Gibson, O; Tarassenko, L; Neil, A (2005)
AIMS: To evaluate evidence for feasibility, acceptability and cost-effectiveness of diabetes telemedicine applications. METHODS: MEDLINE, EMBASE, PSYCHINFO, CINAHL, Cochrane, and INSPEC were searched using the terms diabetes and telemedicine for clinical studies using electronic transfer of blood glucose results in people with diabetes. The technology used, trial design and clinical outcome measures used were extracted for trials and prospective cohort studies. Randomized controlled trials with HbA(1c) as an outcome were pooled using standard meta-analytical methods. RESULTS: We identified 539 papers among which 32 papers described 10 prospective cohort studies, 12 parallel group randomized controlled trials (RCT), three crossover trials, and one non-parallel group trial. Only two studies described full details of randomization, blinding of outcomes and dropouts and withdrawals. Electronic transfer of glucose results appears feasible in a clinical setting. Only two of the RCTs included more than 100 patients, and only three extended to 1 year. Only one study was designed to show that telemedicine interventions might replace clinic interventions without deterioration in HbA(1c). Results pooled from the nine RCTs with reported data did not provide evidence that the interventions were effective in reducing HbA(1c) (-0.1%, 95% CI -0.4% to 0.04%). CONCLUSIONS: Telemedicine solutions for diabetes care are feasible and acceptable, but evidence for their effectiveness in improving HbA(1c) or reducing costs while maintaining HbA(1c) levels, or improving other aspects of diabetes management is not strong. Further research should seek to understand how telemedicine might enhance educational and self-management interventions and RCTs are required to examine cost-effectiveness.